Willingness to Vaccinate Against COVID-19: The Role of Health Locus of Control and Conspiracy Theories - Pisl, Vojtech; Volavka, Jan; Chvojkova, Edita; Cechova, Katerina; Kavalirova, Gabriela; Vevera, Jan (Frontiers in Psychology, 2021)
Understanding the predictors of willingness to get vaccinated against COVID-19 may aid the resolution of current and future pandemics. We investigate how the readiness to believe conspiracy theories and three dimensions of health locus of control affect the attitude to vaccination. A cross-sectional study was conducted based on data from an online survey of a sample of Czech university students (n=866) collected in January 2021, using multivariate linear regression models and moderation analysis. Sixty-six percent of Czech students wanted to get vaccinated against COVID-19. Forty percent of the variance of willingness to get vaccinated was explained by belief in covid-related conspiracy theories and the powerful others dimension of health locus of control. One sixth of the variance of willingness to get vaccinated was explained by health locus of control, cognitive reflection and digital health literacy. Health locus of control and conspiracy mentality and its predictors are valid predictors of hesitancy to get vaccinated against COVID-19. Campaigns promoting vaccination should target groups specifically vulnerable to conspiracy theories and lacking health locus of control related to powerful others.